2019
DOI: 10.1097/scs.0000000000005751
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Evaluation of Exiting Points of Supraorbital Region Neurovascular Bundles in Patients With Migraine

Abstract: Purpose: To reveal the presence and nature of exiting points of supraorbital region neurovascular structures and determine the distances of those structures to midline with computed tomography images by taking into account gender and sides in patients with migraine. Methods: The study was conducted retrospectively on computed tomography images of 70 migraine and 70 control patients with a mean age of 39.5 ± 13.8 years (range: 18–80). Presence and nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The distances of the foramen and notch from the midline vary among individuals. 19 Our study observed that the foramen midline distance was longer than the notch midline distance, consistent with findings in the literatüre. 4,19 Therefore, evaluation of migraine patients with CT before the intervention, especially in those whose pain originates in the frontal region, helps to necessitate careful preoperative planning to prevent neurovascular injury.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The distances of the foramen and notch from the midline vary among individuals. 19 Our study observed that the foramen midline distance was longer than the notch midline distance, consistent with findings in the literatüre. 4,19 Therefore, evaluation of migraine patients with CT before the intervention, especially in those whose pain originates in the frontal region, helps to necessitate careful preoperative planning to prevent neurovascular injury.…”
Section: Discussionsupporting
confidence: 92%
“…Anatomic variations of the paranasal region in migraine patients were detected in our prior study, where the presence of Haller cells was more common in migraine patients than in control subjects 18 . In addition, although the most common structure in the supraorbital region in migraine patients is a single supraorbital notch, the frequency of absence of foramens/notches and single foramens is around 30% in other migraine studies 19 …”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The first observed that in some cases there is a relation between the presence of the variation and the incidence of migraine appearance. [ 64 ] The second reported a case of headache and acute loss of sight in a patient with retrobulbar optic neuropathy and hemianopsia in the left eye, secondary to left Sphenoethmoidal sinusitis with the presence of inflammation of the Onodi Cells. [ 65 ]…”
Section: Resultsmentioning
confidence: 99%
“…Bakoń, 2009 [64] Patients Thickening of the MS mucosa was found in 50% of patients, a septum in the MS was present in 19.4% of patients, and pneumatization of the middle ethmoid cells was observed in 67.5% of patients. The pneumatization of the middle ethmoid cells was presented bilaterally in 43.2% of cases, while in 12.3% of cases it was located on the left side, and in 13.0% of cases it was located on the right side.…”
Section: Rysz Andmentioning
confidence: 99%